Modes of Interpretation of «The Tragedy of Coriolanus» by W. Shakespeare (Proceedings of Southern Federal University. Philology, 2020)
The paper deals with the hermeneutic approach to drama interpretation on the material of «The Tragedy of Coriolanus» by W. Shakespeare. The offered model includes a two-fold coordinate system: the analysis of the plot from the point of view of its identification, comprehension and attitude formation, on the one hand, and its semantic, pragmatic and stylistic explanation, on the other hand. The application of this approach to understanding of the tragedy in question makes it possible to define the subject of the play, its genre and the main characteristic features of its heroes. This is a semantic aspect of the identification stage of the play. A pragmatic aspect of the identification consists in describing the main evaluative positions of the heroes as expressed in their words and actions. A stylistic aspect of identification allows us to describe the main linguistic means used to create artistic images. The comprehension level of the text analysis viewed semantically is aimed at the reconstruction of its social and historical context explained by scholarly studies of Shakespeare and his epoch. The pragmatic aspect of analysis on the comprehension level is centered around the motives of the characters’ behavior, the logic of their actions, and the inevitability of their fate. The stage of action in interpretation corresponds to formation of attitudes to the meaning of the text connected with the present days. The tragedy of Coriolanus is a story about a great person who intentionally cuts off his ties with reality and about people around him who fail to come to rescue and thus make him perish.Key words: philological hermeneutics, text interpretation, «The Tragedy of Coriolanus», identification, comprehension, attitudes formation.DOI 10.18522/1995-0640-2020-4-12-28